EKSPLORASI PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN SAINS DAN EFEKTIFITASNYA DALAM PEMBELAJARAN: STUDI LITERATUR - Manja, Manja; Fajriana, Nurul; Hasanah, Mauizah (FKIP Universitas Tanjungpura, 2025)
This study explores the utilization of digital media in science education through a systematic literature review approach. The rapid advancement of digital technology has transformed educational practices, particularly in the teaching and learning of science. By analyzing relevant empirical studies published over the last decade, this research aims to identify trends, benefits, challenges, and the effectiveness of various digital media tools in supporting science learning. A total of [insert number, if available] articles were selected based on predefined inclusion criteria and analyzed using thematic content analysis. The findings reveal that digital media enhances student engagement, supports conceptual understanding, and promotes interactive learning environments. However, the successful integration of digital media depends on factors such as teacher competence, infrastructure availability, and pedagogical alignment. This review provides insights for educators, policymakers, and researchers to optimize digital media use in science education and encourages further investigation into context-specific applications. Keywords: Science Learning, Digital Media, Learning Innovation